PENTINGNYA SIKAP RESPEK BAGI PENDIDIK DALAM PEMBELAJARAN - Eliasa, Eva Imania (MAJALAH ILMIAH PEMBELAJARAN, 2011)
The background of this article came from violence cases at schoolwhich encompass physical psychological violence. Some datashow these thoughtful conditions need to be treated immediately toanticipate broader (larger) consequences for teachers, students andeducation word in Indonesia. Teachers use some kinds of abusebehavior forms as a means to make students be discipline.However, these are not such a right way for that purpose. Thereforethey will need an educational practice which is humanist forstudents. One of the supportive aspects for humanistic education isrespect. Respect is an attitude that admits, appreciate views andstand points of students without underestimate them, open to havecommunication with, and not only provide academic valuation butalso psychological security and give them success experiences.More ever, mutual respect is also important in learning activitiesbecause it can improve student learning interests and motivations.In sum, teachers need to have that kind of attitude (respect), so theycan contribute to the attainment of learning goals maximally.